Online interprofessional education facilitation: A scoping review. (1st February 2019) - Evans, Sherryn Maree; Ward, Catherine; Reeves, Scott
Abstract: Introduction: The use of online media to deliver interprofessional education (IPE) is becoming more prevalent across health professions education settings. Facilitation of IPE activities is known to be critical to the effective delivery of IPE, however, specifics about the nature of online IPE facilitation remains unclear. Aim: To explore the health professions education literature to understand the extent, range and nature of research on online IPE facilitation. Methods: Scoping review methodology was used to guide a search of four electronic databases for relevant papers. Of the 2095 abstracts initially identified, after screening of both abstracts and full-text papers, 10 studies were selected for inclusion in this review. Following abstraction of key information from each study, a thematic analysis was undertaken. Results: Three key themes emerged to describe the nature of the IPE facilitation literature: (1) types of online IPE facilitation contributions, (2) the experience of online IPE facilitation and (3) personal outcomes of online IPE facilitation. These IPE facilitation themes were particularly focused on facilitation of interprofessional student teams on an asynchronous basis. Discussion: While the included studies provide some insight into the nature of online IPE facilitation, future research is needed to better understand facilitator contributions, and the facilitation experience and associated outcomes, both relating to synchronous and asynchronous online environments.